Ferns from a Dense Ombrophylous Forest fragment in urban area, Baturité Massif, Ceará, Brazil (Research, Society and Development, 2022)
The state of Ceará presents a great diversity of environmental conditions, from low areas to higher areas, where the remnants of the Atlantic Forest are installed. In these environments, studies on the knowledge of the pteridophyte component are still scarce, with greater attention being paid to the knowledge of the phanerogamic flora. With this, the present work aimed to carry out a survey of the ferns of the Experimental Campus of Environmental Education and Ecology of UECE, in Pacoti-CE, as well as to elaborate an identification key, in order to facilitate their recognition, contributing to the knowledge of the flora vascular system in the state of Ceará. The collections were carried out throughout 2019, through random walks, collecting the specimens that were in the reproductive stage. The collected material was herborized and later deposited in the Herbarium of the Natural History Museum of Ceará Prof. Days of the Rock (MHNCE-HER). Identification was based on identification keys, specialized bibliography, comparison with herbarium specimens and type specimens. Eleven species distributed in ten genera and seven families were cataloged. The most representative families were Pteridaceae (four spp.) and Polypodiaceae (two spp.). The herbaceous habit (81.81%) was the one with the highest richness. All species are native to Brazil and most are endemic. The Atlantic Forest (ten spp.) and the Amazon (nine spp.) were the domains that presented the highest numbers of representatives. The species Adiantum deflectens presented as a new occurrence for the Atlantic Forest. The area has a high number of species of herbs, many species native to Brazil, in addition to proving the importance of floristic inventories for the knowledge of the flora of Ceará.